Evaluating the relationship between cannabis use and IQ in youth and young adults at clinical high risk of psychosis. Issue 3 (30th December 2015) - Buchy, Lisa; Seidman, Larry J.; Cadenhead, Kristin S.; Cannon, Tyrone D.; Cornblatt, Barbara A.; McGlashan, Thomas H.; Perkins, Diana O.; Stone, William; Tsuang, Ming T.; Walker, Elaine F.; Woods, Scott W.; Bearden, Carrie E.; et al.
Abstract: Among people with psychosis, those with a history of cannabis use show better cognitive performance than those who are cannabis naïve. It is unknown whether this pattern is present in youth at clinical high risk (CHR) of psychosis. We evaluated relationships between IQ and cannabis use while controlling for use of other substances known to impact cognition in 678 CHR and 263 healthy control (HC) participants. IQ was estimated using the Vocabulary and Block Design subtests of the Wechsler Abbreviated Scale of Intelligence. Drug and alcohol use severity and frequency were assessed with the Alcohol and Drug Use Scale, and we inquired participants' age at first use. CHR were further separated into early and late age at onset of cannabis use sub-groups, and low-, moderate- and high-frequency sub-groups. No significant differences in IQ emerged between CHR or HC cannabis users vs. non-users, or between use frequency groups. CHR late-onset users showed significantly higher IQ than CHR early-onset users. Age at onset of cannabis use was significantly and positively correlated with IQ in CHR only. Results suggest that age at onset of cannabis may be a more important factor for IQ than use current use or use frequency in CHR. Highlights: Cannabis use and IQ were rated in youth at CHR of psychosis and controls. CHR late-onset users showed significantly higher IQ than CHR early-onset users. Age at cannabis use onset was positively correlated with IQ in CHR youth only. Age at onset of cannabis may be an important factor for IQ in CHR youth.